Artemisinin reduces PTSD-like symptoms, improves synaptic plasticity, and inhibits apoptosis in rats subjected to single prolonged stress - Liu, Qing; Ding, Xiaoyan; Wang, Ying; Chu, Hairong; Guan, Yan; Li, Meng; Sun, Kuisheng (Frontiers in Pharmacology, 2024)
Post-Traumatic Stress Disorder (PTSD) is a chronic mental disorder characterized by symptoms of panic and anxiety, depression, impaired cognitive functioning, and difficulty in social interactions. While the effect of the traditional Chinese medicine artemisinin (AR) on PTSD is unknown, its therapeutic benefits have been demonstrated by studies on models of multiple neurological disorders. This study aimed to extend such findings by investigating the effects of AR administration on a rat model of PTSD induced by a regimen of single prolonged stress (SPS). After rats were subjected to the SPS protocol, AR was administered and its impact on PTSD-like behaviors was evaluated. In the present study, rats were subjected to a multitude of behavioral tests to evaluate behaviors related to anxiety, memory function, and social interactions. The expression of hippocampal synaptic plasticityrelated proteins was detected using Western blot and immunofluorescence. The ultrastructure of synapses was observed under transmission electron microscopy. The apoptosis of hippocampal neurons was examined with Western blot, TUNEL staining, and HE staining. The results showed that AR administration alleviated the PTSD-like phenotypes in SPS rats, including behavior indicative of anxiety, cognitive deficits, and diminished sociability. AR administration was further observed to improve synaptic plasticity and inhibit neuronal apoptosis in SPS rats. These findings suggest that administering AR after the onset of severe traumatic events may alleviate anxiety, cognitive deficits, and impaired social interaction, improve synaptic plasticity, and diminish neuronal apoptosis. Hence, the present study provides evidence for AR's potential as a multi-target agent in the treatment of PTSD.